Peningkatan Kapasitas Usaha Melalui Digitalisasi dan Legalitas Usaha pada Usaha Rumah Panrita Kabupaten Barru: Enhancing Business Capacity through Digitalization and Business Legality in Rumah Panrita, Barru Regency - Rahim, Abd; Syawal, Syawal; Damis, Sariana; Diana, Diana; Wisarna, Wisarna (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Amidst the challenges of competitiveness and the demands of the digital era, MSMEs (Micro, Small, and Medium Enterprises) require strategic interventions to grow. This can involve engaging various parties to help enhance a business's capacity. Academics play a crucial role as a bridge to increase knowledge and facilitate these efforts through community service. This community engagement program aims to strengthen the capacity of the